A contribution to the cranial morphology of Causus rhombeatus (Lichtenstein) with special reference to cranial kinesis - Sulter, M. M.(Mariann Macleod) (Stellenbosch : Stellenbosch University, 2012)
Thesis (M. Sc.) -- Universiteit van Stellenbosch, 1960.